2017
DOI: 10.1016/j.surg.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Surgery investigators funded through the National Institutes of Health: A rebirth

Abstract: Background Funding toward surgical research through the National Institutes of Health (NIH) has decreased relative to other medical specialties. This study was initiated to characterize features of academically successful, surgeon-scientists and departments of surgery. We hypothesized that there may be decreases in young investigators obtaining independent NIH awards and that successful academic departments of surgery may be depending increasingly on PhD faculty. Methods The NIH RePORTER database was queried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Recent data has shown that there was also a 19% decrease in the total amount of NIH-awarded grants to general surgeons from 2003 through 2013 [3]. Furthermore, many surgical subspecialties have noted a gender disparity in those being awarded NIH grants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data has shown that there was also a 19% decrease in the total amount of NIH-awarded grants to general surgeons from 2003 through 2013 [3]. Furthermore, many surgical subspecialties have noted a gender disparity in those being awarded NIH grants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Negotiated “protected time” (such as months or weeks purely devoted to research) can be challenging or even impractical for surgeons 5 . One strategy undertaken by many departments of surgery has been to increase the number of nonclinical faculty dedicated to surgical research, 18 a strategy that is reflected in the findings of this study and others 19 . This strategy allows for departments to engage in the research mission, while continuing to encourage surgeons to be clinically productive.…”
Section: Discussionmentioning
confidence: 97%
“…5 One strategy undertaken by many departments of surgery has been to increase the number of nonclinical faculty dedicated to surgical research, 18 a strategy that is reflected in the findings of this study and others. 19 This strategy allows for departments to engage in the research mission, while continuing to encourage surgeons to be clinically productive. This suggests that surgeon-scientists may struggle to balance research and clinical demands, let alone have time to serve as NIH reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The combination of decreased available funding to surgeons, decreased number of surgeons seeking funding, fewer surgeon-scientist mentors, and increased emphasis on academic surgery as a business has resulted in a marked decrease in surgeon-directed research in recent years. 3,21,23,24 The proportion of surgeons with NIH funding is less than 25% of our nonsurgeon medical colleagues. 23 play a vital role in overcoming some of these challenges in fostering the growth of the next generation of surgeon-scientists.…”
Section: Discussionmentioning
confidence: 99%